Theory of light diffraction by single skeletal muscle fibers. - Yeh, Y (1980)
A theoretical discussion is presented describing the diffraction of laser light by a single fiber of striated muscle. The complete three-dimensional geometry of the fiber has been taken into consideration. The basic repeated unit is taken as the sarcomere of a single myofibril, including its cylindrical geometry. The single fiber is considered as the sum of myofibrils up to the fiber dimensions. When proper phasing is taken into account, three cases of interest are analyzed. (a) When the adjacent myofibrils are totally aligned with respect to their index of refraction regions (e.g., A and I bands), then the diffraction pattern reflects that of a larger striated cylinder with the dimensions of the fiber. (b) When a particular skew plane develops for the myofibril elements, additional Bragg reflection occurs at certain specific sarcomere lengths, and intensity asymmetry amongst the diffracted orders occurs. (c) When the myofibril phasing changes in a random fashion, while all sarcomeres remain at the same length, then intensity decrease is directly related to the phase deviation from a reference phase point. This condition may well describe a fiber undergoing active isometric contraction.